2009
DOI: 10.1111/j.1439-0388.2008.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FABP2 as candidate gene for a fatty acid composition QTL in porcine chromosome 8

Abstract: The objective of this work was to analyse the porcine Fatty acid binding protein 2, intestinal (FABP2) gene as a candidate gene for a fatty acid composition quantitative trait loci (QTL) previously described on porcine chromosome 8 in an Iberian by Landrace F(2) cross (IBMAP). Re-sequencing of the porcine FABP2 gene in three Iberian and eight Landrace parental animals resulted in the identification of three single-nucleotide polymorphisms, all of them localized in intron 1. The polymorphism FABP2:g.412T>C, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Two other studies of our group analyzed positional candidate genes for this QTL, i.e. FABP2 [21] and MTTP [22], but the localization of the QTL was not refined. In addition, QTL for IMF palmitic (C16:0) FA composition have been reported in a Duroc x Large White F 2 cross [13] and for stearic (C18:0) FA in a White Duroc x Erhualian F 2 cross [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other studies of our group analyzed positional candidate genes for this QTL, i.e. FABP2 [21] and MTTP [22], but the localization of the QTL was not refined. In addition, QTL for IMF palmitic (C16:0) FA composition have been reported in a Duroc x Large White F 2 cross [13] and for stearic (C18:0) FA in a White Duroc x Erhualian F 2 cross [14].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 470 animals were genotyped for 144 SNPs located on SSC8; these include a selection of 142 informative SNPs derived from the Porcine SNP60K BeadChip [20] and two SNPs that corresponded to the previously detected polymorphisms in the FABP2 [21] and MTTP [22] genes. These SNPs [See Additional file 1: Table S1] were included in a custom-generated panel, genotyped using a Veracode Golden Gate Genotyping Kit (Illumina Inc.) and analyzed with a Bead Xpress Reader (Illumina Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRI-MAP version 2.503, developed by Evans and Maddox [http://www.animalgenome.org/bioinfo/tools/share/crimap], was used to build the linkage map using the genotype information of SSC8. In addition, previously detected polymorphisms in the MTTP and FABP2 genes were also included in the analysis [8], [17]. Raw data had a high genotyping quality (call rate >0.99) and, after selecting SNPs with MAF >5%, markers with genotyping and mapping errors were excluded by using the “Chrompic” option of CRI-MAP and R scripts developed by our group.…”
Section: Methodsmentioning
confidence: 99%
“…Two of them are FAPB3 and FABP4 which also well known as H-FABP and A-FABP, respectively. FABPs act mainly as FA transporters in the metabolic pathway (Estelle et al, 2009), where the peroxisome proliferators-activated receptor (PPAR) family members cooperatively participate as transcription factors. The knock-out mouse study indicated that FAPB3 gene is important for FA transportation and metabolism (Binas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%